189k views
1 vote
Simplify: (–8) • (6) – (5) • (–2)

Simplify: (–4) • (9) – (5) • (–2)

Evaluate 3(a – 4b) when a = –2 and b = 5.

Evaluate 4(a – 3b) when a = –4 and b = 6.

Evaluate 5(a – 2b) when a = –3 and b = 5.

2 Answers

4 votes

Hi!

Simplify: (–8) • (6) – (5) • (–2)

Using PEMDAS

Multiplication

(when you multiply two negatives, you get a positive,

when you multiply one negative and a positive, you get a negative)

-8 * 6 = -48

-5 * -2 = 10

-48 + 10

Subtraction

(imagine a number line)

-48 - 10 = -38

Simplify: (–4) • (9) – (5) • (–2)

Multiplication

-4 * 9 = -36

-5 * -2 = 10

-36 + 10

Subtraction

-36 - 10 = -26

Evaluate 4(a – 3b) when a = –4 and b = 6.

Put in the values, then solve.

4(-4 - 3 * 6)

Solve using PEMDAS

4(-4 - 18)

4 * -22 = -88

Evaluate 5(a – 2b) when a = –3 and b = 5.

5(-3 - 2 * 5)

5(-3 - 10)

5 * -13 = -65

The answers are

-38

-26

-88

-65

Hope this helps! :)

-Peredhel

User Tronious
by
6.5k points
6 votes

(–8) • (6) – (5) • (–2)

= (-8*6)-(5*-2)

= (-48)-(-10)

= -48+10

= -38

(–4) • (9) – (5) • (–2)

= (-4*9)-(5*-2)

= (-36)-(-10)

= -36+10

= -26

Evaluate 3(a – 4b) when a = –2 and b = 5.

= 3[-2 - 4(5)]

= 3[-2 -20]

= 3(-22)

= -66

Evaluate 4(a – 3b) when a = –4 and b = 6.

= 4[-4 - 3(6)]

= 4[-4 -18]

= 4(-22)

= -88

Evaluate 5(a – 2b) when a = –3 and b = 5.

= 5[-3 - 2(5)]

= 5(-3 - 10)

= 5(-13)

= -65

User Andrew Durward
by
6.4k points